Land degradation and gully development in arid environments deduced by mezzo- and micro-scale 3-D quantification – The Negev Highlands as a case study. (June 2018) - Zweig, Rachel; Filin, Sagi; Avni, Yoav; Sagy, Amir; Mushkin, Amit
Abstract: We study in this paper land degradation processes in arid environments that are leading to a major environmental change. These processes, which are mostly the outcome of gully development, have direct impact on agriculture potential, biomass degradation, and escalating desertification. Three representative sites within the Negev Highland, Israel, are studied by utilizing terrestrial laser scans to gain detailed spatial information, accurate estimations, and concisely document overarching trends. The resulting information allows us to thoroughly characterize and quantify the geomorphic and vegetative changes and to calibrate rates and trends that have only been roughly estimated thus far. The scans, which were taken over a four-year span (2009–2013), cover three different types of hydrological seasons and provide unique insights on development rates and subsequent ramifications. The characteristic progression of natural land degradation in the Negev Highlands and the techniques used to document and analyze it can be extended globally to regions undergoing similar transitions. Highlights: We study land degradation processes in arid environments using high-resolution 3-D laser data. The data reveal patterns and driving forces which were not documented thus far. We analyze intra and inter-site relation over different hydrological seasons. Results are referenced to 20 years of coarse monitoring.